Sectoral Growth Effects of Energy Policies in an Increasing-Varieties Model of the Swiss Economy - Lucas Bretschger; Roger Ramer (Swiss Journal of Economics and Statistics, 2012)
The paper applies a theoretical model with increasing capital varieties to study the impact of energy on growth. It translates a multisectoral framework version to a computable general equilibrium (CGE) model of the Swiss economy. We study the impacts of a policy aiming at enabling the economy to reach the longterm target of a 2000-Watt-society, implying a substantial reduction of the energy input in the future. We find that (i) the aggregate effects of an ambitious energy efficiency policy turn out to be moderate, (ii) all sectors in the economy continue to grow at robust positive rates (although growth rates decrease in some sectors compared to business-as-usual), and (iii) some industries experience substantially higher growth under regulation. We focus on the different sectoral growth effects to simulate future structural change.
Keywords: Q54; C63; O41; Q43; 330; Energy and Growth; CGE model; sectoral growth rates; Swiss data